EDUKASI GENERASI Z (DIGITAL) DAN POLA KEHIDUPAN BARU MENGHADAPI MASA NEW NORMAL - Intan Kumalasari; Maliha Amin; Herawati Jaya; Ratna Ningsih (LPPM Univ. Ibn Khaldun Bogor, 2021)
The government's decision to reopen schools and campuses after the Covid-19 pandemic requires readiness, especially for adolescents, who are mostly students. On the one hand, adolescents feel happy with the reopening of offline learning activities, but on the other hand there are fears and worries about their personal safety. Based on the analysis of the situation in the field of indecision faced by adolescents due to the lack of studies on the impact of the new normal if applied in Indonesia. In addition, the lack of outreach from the government on the policies that have been stipulated makes the public confused, so that their implementation is not appropriate. The purpose of this activity is to provide an understanding to adolescents about the new normal and preparations for the new normal. The method used in this activity is health education through online seminars. The results of this activity indicate that most of the adolescents are ready to face the new normal period and are ready to become agents of change for their peers. The results of this activity can also provide input for schools, campuses and managers to work hand in hand to prepare schools and campuses ready for the new normal by providing repeated understanding of new habits that must be adopted in the new normal period regularly so that schools and new campuses are normal. can be realized.